PROGNOSTIC SIGNIFICANCE OF SERUM L-FUCOSE LEVEL IN HEAD AND NECK MALIGNANCIES - RATHAN SHETTY K. S; ARUNAVA KALI (International Journal of Pharma and Bio Sciences, 2014)
India contributes a major pool of head and neck cancer (HNC) patients in global cancer burden. Measurement of L-fucose glycoprotein has been used as a cancer biomarker. In this study, preoperative levels of serum L-fucose glycoprotein were compared with that of postoperative levels measured at 3rd week in 50 HNC patients without distant metastasis. The mean value of serum glycoprotein L fucose was 11.33±7.39 mg % preoperatively. Well differentiated & moderately differentiated squamous cell carcinoma showed a significant drop in postoperative serum L-fucose level. Compared to stage III & IV HNC, serum glycoprotein L fucose level decreased considerably in stage I & II cancers following surgery. In conclusion, head & neck malignancies are associated with a serum glycoprotein L-fucose level exceeding the normal value. In conjunction with clinical diagnostic procedures it can be employed successfully in monitoring patients in postoperative period for complications and recurrence.